Tumor-Infiltrating Lymphocytes in Wilms Tumor - Yadav, Devendra Kumar; Jain, Vishesh; Dinda, Amit Kumar; Agarwala, Sandeep (Indian Journal of Medical and Paediatric Oncology, 2020)
Purpose: T-lymphocytes-infiltrating tumors (TILs) are white blood cells (CD3+) found within the tumor and are thought to indicate a T-cell-mediated specific immune response. The purpose was to evaluate the presence and the subtypes of TILs in Wilms tumor (WT) specimens. Materials and Methods: A prospective study was conducted, and consecutive cases of WT registered and treated at our center were included in the study. The resected tumor was processed by taking multiple sections from the tumor and the peritumoral area. The sections were then processed for evaluating TILs and their subtypes (CD4 + and CD8+). TILs were assessed as a percentage of the total mononuclear cell infiltration in both these areas in all specimens. Results: Twenty-four consecutive specimens of WT were studied. The mean TILs (CD3+) counts was significantly higher (P = 0.001) in the peritumoral area (22.64 ± 1.42; range 20.2%–25%) as compared to the tumor (21.08 ± 2.42; range 14.6%–23.1%). The mean T-Helper (CD4+) counts was also significantly higher (P < 0.001) in the peritumoral area (13.04 ± 1.79; range 10.5%–16.5%) than in the tumor (7.30 ± 1.81; range 4.2%–10.1%). The mean cytolytic T-lymphocytes (CTLs-CD8+) counts in peritumoral area were 6.64 ± 1.09 (range 4.2%–9.2%), while in the tumor, it was 11.96 ± 3.09 (range 3.6%–16.4%). Two patients died on follow-up due to recurrence. These patients showed a markedly lower CD8+ cell count and higher CD4+/CD8+ ratio in the tumor. Conclusion: T-cells infiltration takes place in WT, and most of the patients demonstrate a higher concentration of CTL (CD8+) in the tumor as compared to the peritumoral area.
Keywords: Immunosurveillance; tumor-infiltrating lymphocytes; Wilms tumor